Micro/Nano Bubble Technology : Characteristics and Implications Biology Performance of Koi Cyprinus carpio in Recirculation Aquaculture System (RAS) - Henry Kasmanhadi Saputra; Kukuh Nirmala; Eddy Supriyono; Nurul Taufiqu Rochman (Journal Omni-Akuatika)
Technology for aquaculture is growing with the high demand of fish. Micro / nano bubble is one of technology that is developed to increase dissolved oxygen in water. This technology is used to increase Koi fish production in high density via RAS. The purpose of this study was to determine the characteristics of micro / nano bubble technology and its effect on biology of koi fish (Cyprinus carpio). Lutor was used to introduce micro / nano bubble in the fish tank by using fish length (e.g. 7.49 ± 0.29 cm). This research used completely randomized design with one factor (fish density) and three replications. This factor was three densities of fish at 15 fish.60 L-1 (A), 30 fish.60 L -1 (B), and 45 fish. 60 L -1 (C). The result showed that there was the absolute length of each treatments was (0.52 ± 0.03a) cm for A, treatment  B (0.36 ± 0.07ab) cm and C treatment (0.29 ± 0.08b) cm. The best treatment is A treatment (15 fish. 60 L -1) and different significant in statistic with C treatment (45 fish. 60 L-1) but not significant in statistic with B treatment (30 fish. 60 L -1).